Aplicativo de terapia miofuncional orofacial para idosos usuários de próteses dentárias - Sousa, Clara Franciely da Mota (2024)
Introduction: The global demographic landscape has shown a significant increase in the elderly population, and the physiological, psychological, physical, morphological, and biochemical changes in this age group pose a significant challenge. The loss of dental elements resulting from inappropriate habits and limitations over the years leads to anatomical, aesthetic, and functional alterations in individuals. Orofacial myofunctional therapy can contribute to dental rehabilitation by facilitating the adaptation of prostheses and developing appropriate structural patterns to avoid inadequate compensatory mechanisms. Objectives: – Identify, in the literature, scientific evidence regarding the impact of prosthetic rehabilitation on the orofacial myofunctional condition of complete and/or partial edentulous individuals; Construct a mobile application for orofacial myofunctional therapy targeting elderly denture users; Validate the content of the application through expert judges; Method: This study consists of three methodological stages: The first involves a systematic review to identify the orofacial myofunctional condition in denture users in the scientific literature. In the second stage, a mobile application with orofacial myofunctional exercises based on scientific evidence found in the first phase was developed, targeting elderly individuals using dentures. Finally, in the third stage, the application’s content was validated through the assessment of experts, who are professionals with qualifications in Speech-Language Pathology and a minimum master’s and/or specialization degree in Orofacial Myofunctional Therapy. Results and Discussion: The following were produced: 1) A systematic review article titled “Orofacial Myofunctional Condition in Denture Users,” which demonstrates the structural and functional changes resulting from edentulism and the possibility of restoring the balance of the Stomatognathic System through orofacial myofunctional therapy; 2) An application developed based on the systematic review and literature findings, emphasizing the importance of performing myofunctional exercises that promote the mobility of lips, tongue, and cheeks, in addition to the rehabilitation of functional activities in elderly individuals with dentures; 3) Validation of the TREINAFACE application’s content by eight experts, using the content validation method (CVM). Final Considerations: The systematic literature review allowed for the consolidation of knowledge about orofacial myofunctional conditions in denture users and the structural alterations resulting from tooth loss, affecting the pattern and execution of chewing, swallowing, and speech functions. The validation of the application’s content by experts provided greater reliability in the development of this dissertation’s technological product, highlighting its relevance for speech therapists in planning the best orofacial myofunctional therapy strategies for elderly individuals with dentures, promoting parameters of comfort, well-being, autonomy, and quality of life.